Aplicação e avaliação de conceitos do pensamento computacional em pacientes de um hospital pediátrico - Oliveira, Jussara Siqueira De [UNIFESP] (2018)
INTRODUCTION: Pediatric patients have their autonomy, social and cultural interactions are limited to the hospital routine. the digital artifacts found in mobile applications are shown as an option that can assist subject in building their knowledge. OBJECTIVE: To evaluate the use of software available in a mobile application for learning concepts of computational thinking and its influence on cognitive performance in patients of a pediatric hospital. METHOD: Based on the data obtained in the profile evaluation of the target audience, we formulated the tasks developed during the workshops, in which the subjects used Scratchjr to create games and animations. at the end of the workshops, we analyzed the artifacts created, interviewed the patients to verify the use of tools related to the concepts of computational thinking. in order to evaluate the participants' intellectual capacity, we used the WISCIII scale before and after the workshops. RESULTS: Participants demonstrated learning of the concepts of computational thinking during the workshops and showed improvement in the performance of the WISCIII scale. CONCLUSION: The didactic sequence positively influenced the learning process of the concepts of computational thinking and the cognitive performance of the patients of a pediatric hospital participating in the research.